CYBERSEX ONLINE ACTIVITIES AMONG STUDENTS IN YOGYAKARTA - Suciati,; Amalia, Ayu (International Journal of Psychosocial Rehabilitation, 2020)
Objective of this research, to describe intensity on accessing cybersex online accounts, especially on mobile messenger application. The respondents of our research are students living and studying in Yogyakarta. This research applies predominantly descriptive quantitative method, but also includes data collection techniques using questionnaires. The sampling technique in this study is based on convenience sampling and a validity test was conducted on 62 respondents, that represents college students across Yogyakarta, as a region whereas this research conducted, with a tangible level of 5%. Online platform observed and analysed by this research is mobile messenger application known as LINE by Naver, specifically on frequency, intensity and content preference that moulds the pattern this particular mobile messenger application usage by respondents. Research finding proves that there is a slightly significant difference on the intensity of accessing cybersex on official LINE accounts between male and female respondents, with higher tendency to access cybersex online accounts by female respondents. Engaging in sexual activities on the network, female respondents seem to prefer online activities that involving textual interaction, chat, and dialogue. Female respondents have a high interest in cybersex through messenger application, textual expressions and connect to dating services which emphasize on erotic dialogues, objectifying sexual desire. While male respondents indulge in cybersex online activities through cybersex online accounts, specializing on messenger sites that provide pictures or videos with pornographic contents. Anonymity conducted by respondents while using cybersex online account, accommodate their freedom to occupy cybersex online account services to comply their sexual needs.